2020
DOI: 10.21203/rs.2.19501/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of a pre- and post- operative exercise programme versus standard care on physical fitness of patients with oesophageal and gastric cancer undergoing neoadjuvant treatment prior to surgery (The PERIOP-OG Trial): Study protocol for a randomised controlled trial.

Abstract: Background: Advances in peri-operative oncological treatment, surgery and peri-operative care have improved survival for patients with oesophagogastric cancers. Neoadjuvant cancer treatment (NCT) reduces physical fitness, which may reduce both compliance and tolerance of NCT as well as compromising post-operative outcomes. This is particularly detrimental in a patient group where malnutrition is common and surgery is demanding. The aim of this trial is to assess the effect on physical fitness and clinical outc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…20) In particular, subgroup analyses showed that the relationship between gait speed and incident CVD is more pronounced in female or elderly patients, suggesting that these subgroups could be more adequate targets for rehabilitation. Currently, there are many on-going studies examining the efficacy of rehabilitation in patients with cancer, [21][22][23] and we need to accumulate clinical data regarding the impact (not only efficacy but also safety) of rehabilitation on CVD outcomes in cancer survivors. Recently, a comprehensive model (i.e., cardiac oncology rehabilitation [CORE]) has been proposed to prevent or reduce cardiovascular events using a multimodality approach of cardiac rehabilitation in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…20) In particular, subgroup analyses showed that the relationship between gait speed and incident CVD is more pronounced in female or elderly patients, suggesting that these subgroups could be more adequate targets for rehabilitation. Currently, there are many on-going studies examining the efficacy of rehabilitation in patients with cancer, [21][22][23] and we need to accumulate clinical data regarding the impact (not only efficacy but also safety) of rehabilitation on CVD outcomes in cancer survivors. Recently, a comprehensive model (i.e., cardiac oncology rehabilitation [CORE]) has been proposed to prevent or reduce cardiovascular events using a multimodality approach of cardiac rehabilitation in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of the impact of exercise therapy on surgical fitness after neoadjuvant chemotherapy, in the randomised prospective setting, may be beneficial. The PERIOP-OG trial is an RCT designed to investigate this in a cohort of 72 participants with upper gastrointestinal cancers, and results are awaited [37] (NCT03807518).…”
Section: Neoadjuvant Chemotherapy and Fitness For Surgerymentioning
confidence: 99%